Study the association of demographic factors and health status of construction workers - Gupta, Anurag; Gokhale, Ramakanth M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Objectives of the study was to study socio-demographic profile of construction workers and to study association of demographic factors to health status of construction workers. Methods: A cross sectional study was conducted at various construction sites. The study included 300 construction workers, aged >14 years and who were willing to participate in the study. Worker’s Medical and occupational history was taken. Data was analysed using software Open-Epi version 2.3.1 and Microsoft Excel 2010. Chi-square test and Fisher Exact test were performed to detect he statistical significance. Results: The mean age of workers was 28.02±8.19 years. Majority (52.33%) of the workers belonged to the age group of 15-25 years. Majority (82.67%) workers were males. 198 (66.00%) of workers were married. 224 (74.67%) belonged to Hindu religion and 60 (20%) were Muslim. 224 (74.67%) of workers were literate. Laborers constituted 204 (68%) of work force. 183 (61.00%) had duration in this occupation, less than 5 years. Majority i.e. 289 (96.33%) of the workers belonged to class IV (Upper Lower Class). Age, marital status, type of occupation and duration in the occupation are found to be significantly associated with the health of the worker. Conclusions: Age, marital status, type of occupation and duration in the occupation are found to be significantly associated with the health status of the workers. Behavioral Change Communication activities should be actively carried out site to impart education about occupational health hazards and means to prevent them. Periodic health check-up of construction workers should be carried out.